2018
DOI: 10.1007/s40264-018-0638-2
|View full text |Cite
|
Sign up to set email alerts
|

The Uncertainty of the Association Between Proton Pump Inhibitor Use and the Risk of Dementia: Prescription Sequence Symmetry Analysis Using a Korean Healthcare Database Between 2002 and 2013

Abstract: The risk of PPIs being associated with dementia may be overestimated. Further pharmacoepidemiological studies are needed to identify the risk of dementia with PPI use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Effects of statins are likely due to underlying conditions outweighing the effects of medications (cardiovascular disease, metabolic syndrome), not unlike the insulin case described above. Association of anti-acids may need to be deconvoluted further in the effects of soluble aluminium and proton-pump inhibitors [57]. Overall, the profile of REG distribution coefficients between the top and the remaining octiles of REG rank for 1033 individual dosage forms agrees with literature and the observed coefficients can be rationalized through the balance between the effects of therapy and that of underlying cause on the incidence of cognitive decline.…”
Section: Screening Of Individual Pharmacological Mechanisms For Corresupporting
confidence: 64%
See 1 more Smart Citation
“…Effects of statins are likely due to underlying conditions outweighing the effects of medications (cardiovascular disease, metabolic syndrome), not unlike the insulin case described above. Association of anti-acids may need to be deconvoluted further in the effects of soluble aluminium and proton-pump inhibitors [57]. Overall, the profile of REG distribution coefficients between the top and the remaining octiles of REG rank for 1033 individual dosage forms agrees with literature and the observed coefficients can be rationalized through the balance between the effects of therapy and that of underlying cause on the incidence of cognitive decline.…”
Section: Screening Of Individual Pharmacological Mechanisms For Corresupporting
confidence: 64%
“…Thus, PDE5 inhibitors [42], antiplatelet [43,44], vasodilators [43,45], antimigraine [38,39], antivirals [46], probiotics [47], magnesium [48,49], transdermal oestrogen ( Table 2) and possibly metformin [40,41,50,51] are the agents of interest to perhaps combine with the multivitamin-multimineral formulas of Table 2. Conversely, the signals by corticosteroids [52,53], anti-cancer therapies [54,55], anti-acid drugs [56,57], infections underlying use of antibiotics and antifungals [58], the link between dementia and respiratory deficiency [59], between dementia and cardiac arrythmia [44] mostly align with outside evidence of involvement in neurodegeneration. Effects of statins are likely due to underlying conditions outweighing the effects of medications (cardiovascular disease, metabolic syndrome), not unlike the insulin case described above.…”
Section: Screening Of Individual Pharmacological Mechanisms For Corrementioning
confidence: 99%
“…However, these results were questioned. Some studies from healthcare databases, such as the Korean Healthcare Database [31] and the National Alzheimer's Coordinating Center (NACC) database, [20] do not support the claim that PPI use is associated with a greater risk of dementia. Their findings are in line with those of a Finnish nationwide nested case–control study conducted by Taipale et al, [32] which assessed the impact of the lag window between exposure and outcome, finding no clinically meaningful relation between PPI use and the risk of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There is a well-recognized epidemiological link between PPIs and the increased risk of dementia [2, 3]. However, many studies have reported that PPIs are not associated with a greater risk of dementia or AD [4, 5]. But the evidence for this is limited.…”
mentioning
confidence: 99%
“…However, recently, Gray et al [4] reported that PPI use is not associated with dementia risk, even for people with high cumulative exposure in a prospective population-based study. A prescription sequence symmetry analysis conducted by Park et al [5] also indicated that the risk of PPIs being associated with dementia may be overestimated. This recent controversial report challenges whether or not PPIs are indeed associated with dementia.…”
mentioning
confidence: 99%